TOXICO-PATHOLOGICAL ASSESSEMENT OF Nerium oleander ROOTS AND LEAVES ON WISTAR RAT - MAAROUF, TOUNES; OTMANI, INES; TALBI, AMINA; HAMAMDIA, ZAHRA; BENDALI-SAOUDI, FATIHA; ABDENNOUR, CHERIF (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The aim of the study was to evaluate the toxic effects of Nerium oleander roots (R) and leaves (L) aqueous extract on Wistar rat. Serum chemistry, epididymal sperm parameters and histological examination of liver, kidney and brain were assessed after twelve consecutive day’s oral administration of N. oleander. The extracts of R1, R2, L1 and L2 induced no treatment-related adverse effects with regard to general behaviors, hematological, serum chemistry, epididymal sperm parameters and histological profiles of liver, kidney and brain. However, the higher doses (R3, L3) led to, diarrhea, weakness, anorexia, frequent urination, and nasal hemorrhage, with no mortality. The hematological data revealed a significant increase in the levels of hematocrit and platelets in both L3 and R3 compared to the control. However, these two extracts have not affected the level of RBC, hemoglobin, WBC, and lymphocytes, while the L3 has reduced the concentration of glucose and increased that of urea. However, triglycerides, total cholesterol, alanine aminotransferease, albumin, conjugated bilirubin, potassium and calcium levels of L3 and R3 were not statistically significant compared to the control. Simultaneously bilirubin concentration was increased significantly in L3 and R3. There were no significant differences in epididymal sperm analysis when compared to the control. Adverse histological changes were observed in both liver and kidney as well as in the brain. To conclude, N. oleander extracts have disturbed the levels of certain vital variables in rats at higher dose, in which caution should be taken during the use of this plant.